Old does not mean easy, like this integral.

Calculus Level 5

0 2 2 arcsin x x d x = a b G + c d π k ln ( m ) , \int_0^{\frac{\sqrt{2} }{2} } \frac{\arcsin x}{x} dx = \frac{a}{b}G +\frac{c}{d}\pi^k \ln(m),

where a , b , c , d , k , m a,b,c,d,k,m are positive integers and gcd ( a , b ) = gcd ( c , d ) = 1 \gcd(a,b)=\gcd(c,d)=1 , and G G is the Catalan constant.

Find a + b + c + d + k + m a+b+c+d+k+m .


Note: The Catalan constant G G is defined by G = n = 0 ( 1 ) n ( 2 n + 1 ) 2 . G=\sum_{n=0}^{\infty} \frac{(-1)^n}{(2n+1)^2}.


The answer is 15.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Karthik Kannan
Jul 18, 2014

Let us first substitute x = sin θ x=\sin \theta . Our integral now becomes:

0 π / 4 θ cot θ d θ = I (say) \displaystyle\int_{0}^{\pi/4} \theta\cot \theta\text{ }\text{d}\theta=\mathfrak{I}\text{(say)}

Now we shall use integration by parts:

I = θ ln sin θ 0 π / 4 0 π / 4 ln sin θ d θ \mathfrak{I}=\left.\theta\ln \sin \theta\right|_{0}^{\pi/4}-\displaystyle\int_{0}^{\pi/4} \ln \sin \theta\text{ }\text{d}\theta

I = π 8 ln 2 0 π / 4 ln sin θ d θ \therefore \mathfrak{I}=-\dfrac{\pi}{8}\ln 2-\displaystyle\int_{0}^{\pi/4} \ln \sin \theta\text{ }\text{d}\theta

Now consider the Taylor expansion of ( ln ( 1 x ) ) \bigg(-\ln (1-x)\bigg) :

ln ( 1 x ) = x + x 2 2 + x 3 3 + . . . -\ln (1-x)=x+\dfrac{x^2}{2}+\dfrac{x^3}{3}+...

Replacing x x by e i 2 θ e^{i2\theta} we get:

ln ( 2 sin θ ) i ( θ π 2 ) = r = 1 e i 2 r θ r -\ln (2\sin \theta)-i\bigg( \theta-\dfrac{\pi}{2}\bigg)=\displaystyle\sum_{r=1}^{\infty} \frac{e^{i2r\theta}}{r}

Comparing the real parts on both sides we get:

ln sin θ = ( r = 1 cos 2 r θ r ) ln 2 \ln \sin \theta=-\bigg( \displaystyle\sum_{r=1}^{\infty} \frac{\cos 2r\theta}{r}\bigg)-\ln 2

Thus 0 π / 4 ln sin θ d θ = 0 π / 4 ( ( r = 1 cos 2 r θ r ) + ln 2 ) d θ \displaystyle\int_{0}^{\pi/4} \ln \sin \theta\text{ }\text{d}\theta=-\displaystyle\int_{0}^{\pi/4} \Bigg( \bigg( \displaystyle\sum_{r=1}^{\infty} \frac{\cos 2r\theta}{r}\bigg)+\ln 2\Bigg)\text{d}\theta

= ( ( 1 2 r = 1 sin r π 2 r 2 ) + π 4 ln 2 ) =-\Bigg( \bigg( \dfrac{1}{2}\displaystyle\sum_{r=1}^{\infty} \frac{\sin \dfrac{r\pi}{2}}{r^2}\bigg)+\dfrac{\pi}{4}\ln 2\Bigg)

= ( G 2 + π 4 ln 2 ) =-\bigg( \dfrac{G}{2}+\dfrac{\pi}{4}\ln 2\bigg)

Thus I = G 2 + π 8 ln 2 \mathfrak{I}=\boxed{\dfrac{G}{2}+\dfrac{\pi}{8}\ln 2}

There is an elementary way. Set I = 0 π / 4 ln ( cos x ) d x I=\int_0^{\pi/4}\ln(\cos x)\,dx and J = 0 π / 4 ln ( sin x ) d x J=\int_0^{\pi/4}\ln(\sin x)\,dx then find I + J I+J and I J I-J .

Anastasiya Romanova - 6 years, 6 months ago

Nicely done! :)

Pranav Arora - 6 years, 10 months ago

Nice one! Really nice idea.

jatin yadav - 6 years, 10 months ago
Jatin Yadav
Jul 26, 2014

Firstly, it is quite easy to show that:

G = n = 0 ( 1 ) n ( 2 n + 1 ) 2 = 0 1 1 x 0 x n = 0 ( 1 ) n t 2 n d t G = \displaystyle \sum_{n=0}^{\infty} \dfrac{(-1)^n}{(2n+1)^2} = \displaystyle \int \limits_{0}^{1} \dfrac{1}{x} \int \limits_{0}^{x} \displaystyle \sum_{n = 0}^{\infty} (-1)^n t^{2n} dt

G = 0 1 arctan x x d x \Rightarrow G = \displaystyle \int \limits_{0}^{1} \dfrac{\arctan x}{x} dx

Putting x = tan t , x = \tan t,

G = 0 π / 4 2 t csc 2 t d t G = \displaystyle \int_{0}^{\pi/4} 2t \csc 2t dt

Applying by parts, we get :

G = 0 π / 4 ln ( cot t ) d t G = \displaystyle \int_{0}^{\pi/4} \ln(\cot t) dt

Note: This identity(without proof) is given at the wiki page on Catalan constant.

Now, Let 0 π / 4 ln ( sin t ) d t = I 1 \displaystyle \int_{0}^{\pi/4} \ln(\sin t) dt = I_{1} , and 0 π / 4 ln ( cos t ) d t = I 2 \displaystyle \int_{0}^{\pi/4} \ln(\cos t) dt = I_{2} .

Then, I 1 + I 2 = 0 π / 4 ln ( sin 2 t 2 ) d t = π 2 ln 2 I_{1} + I_{2} = \displaystyle \int_{0}^{\pi/4} \ln\bigg(\dfrac{\sin 2t}{2}\bigg) dt = \dfrac{-\pi}{2} \ln 2

Also, I 2 I 1 = 0 π / 4 ln ( cot t ) d t = G I_{2} - I_{1} = \displaystyle \int_{0}^{\pi/4} \ln(\cot t) dt = G

Hence, we get I 1 = 0 π / 4 ln ( sin t ) d t = π 4 ln 2 G 2 I_{1} = \displaystyle \int_{0}^{\pi/4} \ln(\sin t) dt = -\dfrac{\pi}{4} \ln 2 - \dfrac{G}{2}

Now, Putting x = sin t x= \sin t in I = 0 1 / 2 arcsin x x d x I = \displaystyle \int_{0}^{1/\sqrt{2}} \dfrac{\arcsin x}{x} dx , we get:

I = 0 π / 4 t cot t d t I = \displaystyle \int_{0}^{\pi/4} t \cot t dt

Now, applying by parts, we get:

I = t ln ( sin t ) 0 π / 4 0 π / 4 ln ( sin t ) d t I = t \ln(\sin t) \bigg|_{0}^{\pi/4} - \displaystyle \int_{0}^{\pi/4} \ln(\sin t) dt

= G 2 + π 8 ln ( 2 ) \boxed{\dfrac{G}{2} + \dfrac{\pi}{8} \ln(2)}

Really brilliant idea!! The first step is just too good!! ¨ \ddot\smile

Karthik Kannan - 6 years, 10 months ago
Lu Chee Ket
Oct 28, 2015

0.730181058376564+ determined (1/ 2) G + (Pi/ 8) Ln 2.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...